The role of BCLFA1 in cellular transformation - Shipanga, Hendrina (Division of Medical Biochemistry, 2019)
The malignant transformation of normal cells into cancer cells result in the loss of control of cellular regulatory mechanisms such as loss of function of tumour suppressors and gain of function of oncogenes. Genetic mutations may be inherited or acquired during the process of malignant transformation, such that the normal mechanisms responsible for control cellular proliferation become dysfunctional. Aberrations of the BCLAF1 gene located on chromosome 6q23 has previously been detected by whole genome sequence analysis of DNA from oesophageal cancer biopsies. Although the role of BCLAF1 is not well defined, some studies have shown BCLAF1 to have functional connections linked to some of the known hallmarks of cancer such as cell proliferation, apoptosis and genome stability, thus linking BCLAF1 to cellular transformation. The objective of the study was to examine the effects of BCLAF1 knockdown/BCLAF1 knockout studies in cellular gene expression and tumorigenesis. BCLAF1 expression was significantly reduced in the immortalized keratinocyte cell line (HaCaT), a lung transformed fibroblasts cell line (CT1), cervical cancer cell line (HeLa), breast cancer cell line (MDA-231) and two oesophageal cancer cell lines (KYSE30 and WHCO1), with a highly significant reduction in the breast cancer cell line (MDA-231). siRNA mediated knockdown of BCLAF1 resulted in altered expression of several downstream genes including downregulation the proapoptotic genes Caspase-3 and BAX and the DNA damage repair genes EXO1, ATRIP and BACH1. BCLAF1 deficiency also attenuated P53 expression and slightly increased P21 expression resulting in a P21-dependent G1 phase cell cycle arrest. To our knowledge, this is the first study to identify H2AX as a downstream gene of BCLAF1 that is downregulated by BCLAF1 knockdown. Abrogation of BCLAF1 in CT1 cells resulted in P53-dependent uncontrolled growth of cells, survival and accumulation of apoptosis-resistant cells, and genomic instability; all events that are crucial in tumourigenesis.